The Challenges of Public Innovation: Insights From Risk Governance in Batang Regency - Adyawarman Adyawarman (Magister Administrasi Publik, 2021)
Interest in public sector innovations has been growing among policy makers, practitioners, and scholars. Despite the complexity of modernisation and resource constraints, public leaders must create innovative policies to deliver better services and overcome societal challenges. This research is on public innovation which examined opportunities and challenges facing public innovation. The study was triggered by the mixed outcomes of the decentralisation policy in Indonesia. While some local governments have engaged in service, process and governance innovations, many continue to face difficulties in adopting and sustaining innovative programs. Through case studies of two governance innovations in Batang Regency (2012-2017), this research appraised the dilemma of risk governance in securing the credibility and sustainability of two innovative ideas, namely UPKP2 local ombudsman and Budget Festival. Results of the study highlighted evidence that considering the highly dynamic socio-political environment that heads of local governments face, managing risk governance is important in implementing public innovation in a meaningful and sustainable way